Jekyll and Hyde: Day–night personality differences in the water scorpion Nepa hoffmanni. (23rd February 2023) - Hyun, Hyoseul; Han, Chang S
Abstract: Differences between daytime and night-time behaviors are common in insects due to potential trade-offs between predator avoidance and foraging. While diel effects on average behavior are well documented, it remains unclear whether individuals differ in how they adjust their behavior between daytime and night-time. In this study, we focused on two light dependent behaviors, activity and tonic immobility, in the water scorpion ( Nepa hoffmanni ). Each individual was assayed for each behavior six times during the day and six times at night. Then, we explored diel differences in (1) average behavior, (2) among-individual variation in behavior, (3) individual rank order of behavioral expression, and (4) the sign and magnitude of behavioral syndromes (among-individual correlations between behaviors). At night, N. hoffmanni was more active and exhibited shorter periods of tonic immobility. Among-individual variation in activity was greater at night than during the day, but among-individual variation in tonic immobility did not differ between day and night. Individuals also differed in their diel plasticity in activity but not in tonic immobility. Thus, both (1) day–night differences in among-individual variation and (2) individual variation in diel plasticity contributed to the light-dependent sign of the behavioral syndromes. Our findings highlight the need for individual-level studies to fully elucidate diel influences on animal behavior. We suggest that day–night differences in behavioral syndromes as well as in selection might be key to behavioral evolution, especially in animals active during both day and night. Abstract : Diel period significantly influenced the average behavior of water scorpions; they were more active but had decreased antipredator responses at night. Individuals also differed in their response to diel period, which resulted in differences in behavioral variation and correlations between day and night. We highlight the need for individual-level studies to fully elucidate diel influences on animal behavior.